Investigating polygenic risk scores in Alzheimer's disease - Chaudhury, Sultan Raja (2024)
Alzheimer’s disease (AD), the most common cause of dementia, is one of the most studied diseases in the UK due to its impact on quality of life, symptoms of neurodegeneration, and burden on health and social care. AD is most common in the elderly, as age is a significant risk factor, but can also be found in young people. Diagnosis and treatment has developed over the years through improved therapies and screening methods, but a cure or definitive disease prevention has not been found.